Is it reasonable for the use of Rh‐ee blood? A hospital‐based survey from a southern medical center in Taiwan. Issue 1 (14th October 2021) - Hsiao, Hui‐Hua; Yeh, Chi‐Jung; Ting, Shuo‐Chun; Chuang, Tzer‐Ming; Ke, Ya‐Lun; Yeh, Tsung‐Jang; Gau, Yu‐Chin; Du, Jeng‐Shiun; Hsiao, Chi‐En; Wang, Hui‐Ching; Cho, Shih‐Feng; Hsu, Chin‐Mu; et al.
Abstract: Identification of alloantibodies and achieving a reduction in the rate of red blood cell (RBC) alloimmunization are important issues to prevent transfusion complications. The aim of this study was to identify the antigen and alloantibodies in our patients and to study the association of alloimmunization with previous transfusion. Transfusion records from the blood bank of Kaohsiung Medical University Hospital between 2015 and 2017 were retrospectively enrolled in the study. Antigen and antibody identification was performed using routine blood bank methods. In total, 56, 422 transfusion records from 2015 to 2017 were included in the study. Among them, 1858 alloantibody episodes were found in the pre‐transfusion survey, and anti‐Mia, anti‐E, and cold antibodies were the most common alloantibodies, with a prevalence of 3.29% (1858/56, 422). Among them, 130 episodes involved newly found alloantibodies with no alloantibodies found in the previous transfusion survey. Tracing back to these newly transfusion‐induced alloantibodies, the antibody was found with a mean of 10.8 ± 7.8 units of packed RBC transfusion, a mean of 66.3 ± 52.8 days, and with a mean of 4.3 ± 2.7 times of transfusion from the first transfusion therapy. An antibody survey revealed that Rh‐ee (62.1%) was the most common phenotype in these newly identified antibodies. In summary, this hospital‐based study revealed that RBC alloantibody rates were present at rates of 3.29%, with anti‐Mia, anti‐E, and cold antibodies being the most common alloantibodies. Among them, anti‐E was the most commonly developed alloantibody. Given that the Rh‐ee group is the most common phenotype in our population, the strategy of using Rh‐ee blood for Rh‐ee recipients is reasonable for transfusion safety.